Ethics of expert evidence - Millett, Stephan (Lawbook Co., 2013)
The use of expert evidence in courts has been problematic for many years and a focus on the ethics of witnesses has given rise to the widespread introduction of rules governing how experts may behave. But, in addition to the ethics of witnesses, the ethics of expert evidence also encompasses the ethics of lawyers; the financial and other costs of using experts; the use, or misuse, of science; the way claims to truth are made; and the impact on the law itself. In short, despite recent clarification of rules for witnesses, there remain significant issues with how the legal system makes use of expert testimony. This article explores some of those issues.